Knowledge, attitude and practice of adolescent girls on HIV/AIDS: a case study of Lalitpur sub metropolitan city, ward no. 4. - Dhakal, Archana (2008)
ABSTRACT: Acquired immune deficiency syndrome (AIDS) is a disease caused by Human Immune deficiency Virus (HIV). HIV/AIDS is a global problem. It sees no boundary of colour, country and capital. All people in this world i.e. all members of Homo sapiens species are capable of acquiring this disease. HIV/AIDS is not only a health problem but also an economic and human right problem as well. In this survey, it was found that all respondents had heard about HIV/AIDS. All of them knew that unsafe sexual contact transmits HIV while shaking hands does not. Most of them thought that transfusion of blood (92%), birth from infected mother (90%) and use of unsterilized syringe (77%) transmits HIV. Meanwhile, most of them thought that sharing comb, towels (79%); drinking alcohol (73%); while sharing clothes (83%) does not transmit HIV. For preventive measures for HIV/AIDS: all said sex education, increasing awareness, using condoms and checking blood before transfusion; 92% said preventing pregnancy in infected mother. 86% didn't know the place where they can find the antiviral medicine. 35% of respondents think that this disease is preventable; all agreed that it is not a taboo, and that it is necessary for a student to have knowledge and awareness about HIV/AIDS 11% of the respondents had attended AIDS related program and all would surely go to any program on HIV/AIDS. If their friend contracted HIV: 74% said that they would be a caring friend. If they contracted HIV: all said that they would take more care of their health and have positive thinking; 86% said that they would make awareness campaign; 69% said that they would consult a doctor; 43% said they would live life as much as they can; 39% said that they would just be normal. Subsidies or low price should be given to checkup and treatment of HIV/AIDS. The INGOs and NGOs should conduct their awareness program with more rigor and frequency so that all the participants are crystal clear about all aspects of HIV/AIDS. Articles, programs on HIV/AIDS should be made a priority by all medias.